Analisis Penggunaan Platform E-Commerce Dalam Meningkatkan Penjualan Produk Kuliner Nasi Kuning Ibu Yanti Umkm Di Kecamatan Pamulang - Atia Putri Pratama; Lukman Nul’hakim (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract. This research aims to analyze the utilization of e-commerce platforms in increasing the sales of culinary products at the MSME Nasi Kuning Ibu Yanti in Pamulang District. The focus of the research includes the role of e-commerce platforms in supporting marketing, the digital strategies implemented, their impact on sales volume and revenue, and recommendations for optimizing platform utilization. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The findings reveal that the use of the GoFood platform has had a positive impact on increasing daily order volumes, expanding the market reach, and facilitating digital transactions. Promotional strategies such as discounts, bundling packages, and loyalty programs serve as supporting factors in attracting consumer interest. Nevertheless, operational challenges remain, including difficulties in securing drivers, price competition among merchants, service fee deductions, and limited technological proficiency among business owners. Overall, the utilization of e-commerce platforms has proven effective in increasing revenue and expanding market reach for culinary business operators in the digital era. Keywords: E-Commerce, MSME, GoFood, Culinary Sales, Digital Marketing